Beliefs and Rituals Related to Death among Tahtacı Alevis of Yakapınar Village (Journal of Alevism-Bektashism Studies, 2025)
Death has been one of the natural phenomena that individuals and societies have been unable to resist since the beginning of human history. While it is scientifically defined as the cessation of the functions of the circulatory and respiratory systems, societies perceive death primarily as a cultural phenomenon. Beyond its biological dimension, death occupies a significant cultural sphere of meaning and is expressed through the rituals that societies have developed around it. In some cultures, death is not understood as an absolute end; rather, it is interpreted as the beginning of a new state of existence in which the human soul departs from the lived world and embarks on an eternal journey. In the face of this inevitable natural event, societies experience a sense of helplessness and have therefore created rituals surrounding death in order to alleviate this helplessness and ease the pain brought about by loss. The primary purpose of these rituals is to facilitate the deceased’s migration or journey to the “other world” and to mitigate the grief of those left behind. Among the communities that continue to vividly sustain the belief that death is not an end, the Tahtacıs occupy a prominent place. In Tahtacı belief, death is regarded not only as a new beginning but also as a representation of a return to the essence. This understanding is grounded in the belief that human beings were created from God’s own light and, upon death, reunite with Him—that is, with their essence. The fact that death is defined as “walking toward the Truth” (Hakk’a yürümek) in Tahtacı society, and that the consolatory expressions uttered after death symbolically describe the deceased’s migration or journey, demonstrates that this belief continues to be preserved to the present day. In addition to the belief in a return to the essence, the Tahtacı community also maintains the belief that the human soul continues to exist in different realms after death; moreover, it is known that two distinct types of death are recognized within Tahtacı belief. In this article, the Tahtacı community’s interpretations of death and the rituals performed around this phenomenon are examined through the case of Yakapınar Village, one of the three Tahtacı villages located in the Bayındır district of İzmir, using quantitative research methods. The death-related rituals are analyzed comparatively with the death beliefs and rituals of ancient Turkic tradition, and both their contemporary forms of practice and the changes they have undergone are discussed. In order to provide a clearer understanding of the subject and in light of the findings of the literature review, the rituals related to death that constitute the focus of this study are examined under three main headings: pre-death, death, and post-death.